Automated Reconstruction of Complex Object by Integrating Point Clouds and Digital Images - Zhai, Ruifang; Liu, Shanmei; Lin, Chengda (International Information Institute (Tokyo). Information, 2012)
In the current research, unorganized point clouds and digital images are integrated to implement 3D digital reconstruction of complex objects. A registration algorithm of point clouds with different viewpoints under a large rotation angle is proposed. Through this methodology, seamless multiple registrations can be achieved. Meanwhile, digital image sequences are applied for the texture reconstruction of objects, so that the reconstructed object can be demonstrated precisely in geometric features and rich in texture features. The accuracy of the experimental results is assessed, which demonstrates that the proposed methodology is feasible and effective. [PUBLICATION ABSTRACT]